2017
DOI: 10.1111/imr.12608
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of NLRP3

Abstract: A shift in our understanding of macrophage biology has come about as a result of recent discoveries in the area of metabolic reprogramming of macrophages. The NLRP3 inflammasome drives the activation of caspase-1, leading to the production of IL-1β, IL-18, and a type of cell death termed pyroptosis. The NLRP3 inflammasome has been shown to sense metabolites such as palmitate, uric acid, and cholesterol crystals and is inhibited by ketone bodies produced during metabolic flux. The NLRP3 inflammasome has also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
174
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(179 citation statements)
references
References 89 publications
(129 reference statements)
4
174
0
1
Order By: Relevance
“…It has been shown that glycolytic enzymes impact on the inflammasome in macrophages [40]. Hexokinase 1 interacts with voltage-dependent anion channel (VDAC)1 which activates the inflammasome while PKM2 triggers inflammasome activation in a HIF-1α-dependent manner [41] and also activates eukaryotic translation initiation factor 2A kinase, which directly interacts with inflammasome components regulating its assembly [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that glycolytic enzymes impact on the inflammasome in macrophages [40]. Hexokinase 1 interacts with voltage-dependent anion channel (VDAC)1 which activates the inflammasome while PKM2 triggers inflammasome activation in a HIF-1α-dependent manner [41] and also activates eukaryotic translation initiation factor 2A kinase, which directly interacts with inflammasome components regulating its assembly [42].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammasome is a multi‐subunit cytoplasmic complex that catalyzes the proteolytic processing of target substrates via its effector enzyme caspase 1 (Malik and Kanneganti ; Franklin et al . ; Hughes and O'Neill ). In general, the inflammasome is formed by a nucleotide‐binding oligomerization domain‐like receptor (NLR) family member that senses cytoplasmic danger‐associated molecular patterns, the adaptor apoptosis‐associated speck‐like protein containing a carboxy‐terminal CARD (ASC), and pro‐caspase 1 (Lamkanfi and Dixit ) that undergoes autocatalytic cleavage to its active form upon inflammasome assembly (Rathinam and Fitzgerald ).…”
mentioning
confidence: 97%
“…Nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3 or NALP3) is a cytoplasmic sensor that oligomerizes to form a platform known as inflammasome, a protein complex that controls the release of IL-1β and IL-18 by activating caspase-1 [9]. In macrophages, NLRP3 inflammasome activation can be triggered by the pore-forming ionophore nigericin, extracellular ATP, and crystalline substances that induce pyroptosis, a type of cell death [10]. In addition, previous research has shown that some fatty acid-derived lipids, such as the prostaglandin E 2 (PGE 2 ), regulates NLRP3 and the maturation of IL-1β.…”
Section: Introductionmentioning
confidence: 99%